2014
DOI: 10.1155/2014/545493
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as Biomarkers in Rheumatoid Arthritis

Abstract: RA is a complex disease that develops as a series of events often referred to as disease continuum. RA would benefit from novel biomarker development for diagnosis where new biomarkers are still needed (even if progresses have been made with the inclusion of ACPA into the ACR/EULAR 2010 diagnostic criteria) and for prognostic notably in at risk of evolution patients with autoantibody-positive arthralgia. Risk biomarkers for rapid evolution or cardiovascular complications are also highly desirable. Monitoring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
145
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(158 citation statements)
references
References 225 publications
(227 reference statements)
2
145
0
11
Order By: Relevance
“…Proinflammatory cytokines (e.g., TNF, IL-6, IL-1, IFN-g) are abundant in the RA profile, but anti-inflammatory and regulatory cytokines (e.g.,, IL-4, IL-10, IL-13) have also been related to the disease. 51 Most of the biological drugs approved for RA treatment have proinflammatory cytokines as targets, although these agents cannot be used over long time periods. 52 It has been demonstrated that MTX induces IL-6 secretion in human cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines (e.g., TNF, IL-6, IL-1, IFN-g) are abundant in the RA profile, but anti-inflammatory and regulatory cytokines (e.g.,, IL-4, IL-10, IL-13) have also been related to the disease. 51 Most of the biological drugs approved for RA treatment have proinflammatory cytokines as targets, although these agents cannot be used over long time periods. 52 It has been demonstrated that MTX induces IL-6 secretion in human cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, partial and non-responses to these compounds, together with the increasing clinical drive to remission induction, requires that further therapeutic targets are identified [4]. In recent years, a growing number of new cytokines as well as their function in health and disease have been identified [5]. Cytokines serve as the mediators of cellular differentiation, inflammation, immune pathology, and regulation of the immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple biomarkers of disease activity in RA have been evaluated in studies originating from both Africa [6][7][8][9][10][11] and elsewhere [12][13][14][15][16]. In addition, commercial ventures have also focused on developing multi-array test profiles that may improve cost-effective management of RA [15,17].…”
Section: Rheumatoid Arthritis Research In Africamentioning
confidence: 99%